Recent prospects on phosphor-converted LEDs for lighting, displays, phototherapy, and indoor farming - Bispo-Jr, Airton G. [UNESP]; Saraiva, Leonardo F. [UNESP]; Lima, Sergio A.M. [UNESP]; Pires, Ana M. [UNESP]; Davolos, Marian R. [UNESP] (Elsevier, 2021)
Phosphor-converted white-light-emitting diodes (PC-WLEDs) are the main devices behind solid-state lighting (SSL) for both indoor and outdoor lighting, or backlight of liquid-crystal displays (LCD). Nonetheless, despite the current maturity of such devices, some concerns on spectral distribution, reliability, and color qualities of WLEDs for lighting, or even the enhancement of the color gamut of backlight WLEDs still need to be addressed while those achievements lie in the design of high-efficient downshifting converter phosphors featuring thermally-stable luminescence. Additionally, the application of PC-WLEDs in indoor farming and in phototherapy have also been envisaged, however, to fulfill such needs, LEDs are far away in performance compared to those lamps used in lighting. In this context, herein, we overview the state-of-the-art of phosphors able to be used as downshifting converter coatings in LEDs for application in lighting, phototherapy, indoor farming, and phototherapy as well as issues to be overcome and means to achieve it. The main classes of materials discussed here include Eu3+, Eu2+, Ce3+, Mn2+ and/or Mn4+-activated inorganic phosphors, quantum dots, and complexes. Finally, several figures of merit able to qualify the device performance considering photometry, colorimetry, and light impact on human or plant physiology are presented.
Keywords: Indoor farming; Light-emitting diode; Phosphors; Phototherapy; Solid-state lighting